The Effect of Incentives on Employee Job Satisfaction at PT. Landipo Niaga Raya Baubau City - Hasni, Hasni; Yuliningsih, Sri (Institute for Research and Community Service, 2024)
The purpose of this study is to ascertain the impact of sentiment on the job satisfaction of PT. Landipo Niaga Raya Baubau City. The data collection methods employed include field research, library research, correlation, and documentation. The data analysis method employed in this study is a simple linear regression with a sample size of 30 individuals. According to the findings of the research conducted on the impact of sentiment on job satisfaction at PT. Landipo Niaga Raya Baubau, it can be concluded that sentiment has a significant impact on job satisfaction at PT. Landipo Niaga Raya Baubau. The hypothesis was rejected based on the results of the hypothesis test, which involved comparing the value of t to the value of r in the table and conducting a test that determined that t count was greater than t table (2.819>2.05183) or a significance level (Sig) that was greater than or equal to 0.05. As a result, the null hypothesis (Ha) was rejected and the null hypothesis (H0) was accepted. PT. Landipo Niaga Raya Baubau is to increase incentives that influence job satisfaction.